A modalização como um fenômeno semântico-argumentativo e pragmático no gênero projeto pedagógico de curso do ensino superior - Silva, Vanessa Santos da (2024)
The Pedagogical Course Project genre has the function of standardizing and guiding pedagogical actions and tasks, gathering information about the course design, academic, pedagogical and administrative management issues, among other aspects. Considering that this document is essential for higher education, we investigated how the argumentation is constructed in the PPC genre through linguistic-discursive phenomena, especially discursive modalizers, and how they influence the orientations/directions present in the PPC. In this sense, this research has the general objective of investigating the semantic-argumentative and enunciative functioning of the Discursive Modalization phenomenon, present in the Pedagogical Course Project genre of Higher Education, especially undergraduate courses, in different areas of knowledge. As a theoretical contribution, we adopted the studies on Discursive Genres proposed by Bakhtin (2002) and Marcuschi (2008); the Theory of Argumentation in Language, proposed by Ducrot (1987); studies on the phenomenon of Discursive Modalization, based on studies proposed by Lyons (1977), Cervoni (1989), Castilho and Castilho (1993), Koch (2002), Palmer (2009) and Nascimento and Silva (2012). We adopted, as a criterion for classification and data analysis of this research, the classification of discursive modalizers presented by researchers Nascimento and Silva (2012). The investigation has a descriptive nature and interpretative character, as it describes and analyzes the semantic-argumentative functioning of the phenomenon of Modalization in the genre object of study. The research is qualitative, as we bring the subjective character through our interpretative analyses of the discursive modalizers, correlating it with the sociodiscursive function of the PPC genre. Therefore, our corpus is composed of 06 (six) pedagogical projects from different undergraduate courses, covering the following areas of knowledge: Human Sciences; Health Sciences; Exact Sciences, Engineering and Biological Sciences. Within these areas, the PPCs of the courses at the Federal University of Paraíba were selected, namely: Bachelor's Degree in History, Medicine, Computer Science, Gastronomy, Data Science for Business and Materials Engineering. In these documents, we found almost all types of modalizers, with the exception of the Deontic Modalization of Prohibition, as well as the phenomena of co-occurrence of modalizers; we identified the phenomenon of double modal function materialized in a single discursive modalizer. The most frequent modalizers in the PPC genre were the delimiters, evaluatives and the deontic ones of obligation, which are related to the functionality of the PPC genre. Through our analyses, we found different types of meaning effects generated by discursive modalizers, namely: certainty, delimitation, obligation, instruction, axiological value, among others, in our corpus.